The Role of Islamic Education in Countering Radicalism and Extremism among Indonesia's Young Generation - saputra, dedi (Jurnal Ar Ro'is Mandalika (Armada), 2024)
This study examines the role of Islamic education in countering radicalism and extremism among Indonesia's young generation. Indonesia, as a country with the largest Muslim population in the world, faces increasing challenges related to the spread of radical ideologies, particularly among its youth. Utilizing a qualitative approach with a literature study method (library research), this article explores various academic sources, government reports, and research findings to analyze the significance of Islamic education in promoting religious moderation and peace. The study identifies that radicalism often stems from a lack of comprehensive understanding of Islamic teachings, coupled with external influences such as digital media and extremist propaganda. Islamic education, therefore, serves as a vital instrument in fostering values of tolerance, inclusivity, and critical thinking among students. Furthermore, this research highlights the importance of integrating moderate Islamic teachings, such as wasatiyyah (the principle of moderation), into school curricula and pesantren (Islamic boarding schools). Teachers, educators, and Islamic scholars play a critical role in guiding youth to reject extremism by emphasizing compassion, peaceful coexistence, and a proper understanding of religious texts. The study concludes that strengthening Islamic education with a focus on moderation is essential to curbing radical tendencies and creating resilient young generations who can contribute to a harmonious and pluralistic society.